Nieautorytarny autorytet - Bujak, Wojciech (Społeczeństwo, 2022)
John Paul the Second is absolute authority. His character is especially mentioned on the fortieth anniversary of his pilgrimage to Poland. We are currently experiencing a crisis of authorities. What did the Polish pope have in him? What features made him stand out the most. He was a great leader. He had STUDIA I PRACE BADAWCZE Wojciech Bujak – Nieautorytarny autorytet 114 an amazing message. He was firm and consistent. He delighted the crowds. We currently need people like him. We need real authority. In the era of modern mass media, it’s easy to mistake an authority for a celebrity who doesn’t have good role models. John Paul the second has forever entered the history of Poles.